Depression, Anxiety, Coping Skills, and Quality of Life Among Antenatal Women - Siti Roshaidai Mohd Arifin; Nur Aqilah Binti Mohd Abadi; Amalia Kamaruddin; Hazwani Mohd Mohadis; Karimah Hanim Abd Aziz; Ramli Musa; Noor Azimah Muhammad; Khadijah Hasanah Abang Abdullah; Fathima Begum Syed Mohideen; Mohd Fadzli Marhusin; Khairi Che Mat; Hanisah Mohd Noor; et al. (Universiti Putra Malaysia, 2026)
Indexed by SCOPUS/MYCITE